The Effect of the Transtheoretical Model Approach Towards the Body Mass Index of Overweight and Obese Children in Makassar - Kadek Ayu Erika (The Prodia Education and Research Institute (PERI), 2014)
BACKGROUND: Overweight and obesity is now ranked fifth as a global risk for the cause of death. Urban lifestyle is fueled by excessive food intake and lack of activity in overweight and obese children. The assessment of the children’s Body Mass Index (BMI) is one of the indicators to assess the nutritional status of children. One strategy that can be used is the transtheoretical model (TTM) approach which is behavior change that helps children and parents in making more effective decisions to reduce health-risk behaviors among children so that the children’s BMI can decrease. This study aims to identify the differences between children's BMI before and after the TTM approach.METHODS: This research was conducted in the district area of Tamalanrea and Biringkanaya, Makassar. The design used is the Quasy Experiment namely pre- and post-test with control group design. Research subjects were overweight or obese children in the 4th, 5th, and 6th grade of elementary school. The samples in the treatment group consisted of 31 participants, while the control group consisted of 33 participants which were selected using purposive sampling. Intervention research was conducted during a six month period by providing guide books on healthy lifestyle, visiting the families every month using questionnaires, and measurements of children’s height, weight and BMI using WHO’s AntrhoPlus software year 2007.RESULTS: Post-pretest results showed the average value of the treatment group’s BMI was -1.48 and the control group was 1.35. This means that the treatment group experienced a decrease in BMI after the application of TTM. The Mann Whitney test results indicate that there is a difference in the BMI pre-post intervention with the value of p=0.00 (>0.05).CONCLUSION: The overweight and obese children’s BMI was influenced by TTM approach.KEYWORDS: transtheoretical model, children’s BMI, overweight, obesity